AR Sandbox Built Within Unreal Engine 5 - McIntosh, Gareth (Wellington Faculty of Engineering Symposium, 2023)
Augmented Reality (AR) is increasingly recognised as a transformative interface for combining the physical and virtual worlds, thereby elevating user engagement and comprehension of learning topics. This project leverages this capacity through a projection-based AR setup that incorporates a Kinect V2 sensor, a projector, and a box of sand to forge an interactive sandbox environment. In this setup, real-time manipulations inside the physical sandbox have a direct impact on a digitally rendered visualisation that is then projected onto the sand bed. The defining accomplishment of this project is the porting of sandbox software that ran on an outdated OpenFrameworks v0.9.8 to the state-of-the-art Unreal Engine 5 platform. This technological leap accomplishes two objectives: it updates the application with modern visual capabilities and enhances its scalability and overall performance. The transition grants access to a range of advanced graphical features, debugging tools, and an extensive developer community supportive of Unreal Engine 5. Consequently, this means the project has been freed from the maintenance hurdles that were associated with previous attempts to update the OpenFrameworks system to newer versions. This change opens the door for virtually endless possibilities of further features and improvements. With the switch to Unreal Engine 5, the project now has huge potential for innovative changes that could reshape how we interact with the augmented reality sandbox.